Ten-Year Experience of Endoscopic Transanal Resection - Sutton, Christopher D. (2002)
OBJECTIVE: To audit the results of endoscopic transanal resection of tumor (ETAR) performed by a single surgeon at a specialized colorectal unit during a 10- year period. SUMMARY BACKGROUND DATA: A minimally invasive surgical technique, ETAR has enabled much progress to be made in the development of local treatment strategies for rectal neoplasia. It can be used in both the curative and palliative management of rectal lesions and is a treatment option for patients who would be unable to tolerate major surgery. METHODS: The surgical outcome of 104 patients (43 women, 61 men) undergoing ETAR under the care of a single surgeon between 1989 and 1999 was reviewed. Patients were identified from the consultant’s personal records and cross-referenced with operating room logs. Data were collected retrospectively and no patients were lost to follow-up. RESULTS: One hundred four patients underwent 163 procedures during the study period. Follow-up ranged from 6 months to 10 years. Seventy-five patients with a pre-ETAR diagnosis of benign rectal adenoma underwent resection. In 60 patients, the diagnosis was confirmed to be benign; 30 of these were treated with a single resection and 28 with multiple resections. There were two technical failures, both a result of high mobility of the lesion. In no patients did carcinoma subsequently develop. In the remaining 15 patients the final histology demonstrated a malignancy; 9 patients underwent an open surgical rectal resection and 5 had complete endoscopic resection of their lesion. No carcinomas that were fully resected endoscopically have recurred (follow-up 13 months to 8years). The final patient had an extensive rectal cancer and was palliated for 2 months by ETAR. Twelve patients (8 men, 4 women) underwent ETAR for anastomotic strictures; successful treatment was achieved in 11. The one failure was in a Park’s pouch that was subsequently refashioned. Seventeen patients underwent 30 ETARs for palliation of nonresectable rectal adenocarcinoma. Successful palliation of symptoms was achieved in 13 patients and the remainder underwent colostomy formation. One patient died of a myocardial infarction. There were two further complications (blood transfusion for postoperative bleeding, postoperative cerebrovascular accident). CONCLUSIONS: Endoscopic transanal resection of tumor is safe and effective and offers successful palliation or definitive treatment of rectal lesions with low rates of death and complications when performed by a dedicated surgeon.